Mechanistic study on gold(I)‐catalyzed crosscoupling of diazo compounds: A DFT study. Issue 14 (29th December 2017) - Li, Yan; Tian, Ruixue; Liang, Changhai
Abstract: The reaction mechanisms of the gold(I)‐catalyzed cross‐coupling reaction of aryldiazoacetateR1 with vinyldiazoacetateR2 leading to N‐substituted pyrazoles have been theoretically investigated using density functional theory calculations. Two possible reaction mechanisms were examined and discussed. The preferred reaction mechanism (mechanism A) can be characterized by five steps: the formation of the gold carbenoidA2 via the attack of catalyst toR1 (step I), nucleophilic addition of another reactantR2 to generate intermediateA3 (step II), intramolecular cyclization ofA3 to form intermediateA4 (step III), hydrogen migration to give intermediateA5 (step IV), and catalyst elimination affording the final productP1 (step V). Step IV is found to be the rate‐determining step with an overall free energy barrier of 28.3 kcal/mol. Our calculated results are in good agreement with the experimental observations. The present study may provide a useful guide for understanding these kinds of gold(I)‐catalyzed cross‐coupling reactions of diazo compounds. Abstract : Pyrazoles and their derivatives are found as structural motifs in a plethora of compounds from natural products to functional materials and bioactive molecules. Density functional theory calculations can provide a fundamental insight into the reaction mechanisms of the gold(I)‐catalyzed cross‐coupling reaction of aryldiazoacetate with vinyldiazoacetate leading to N‐substituted pyrazoles. The calculated results are in good agreement with experimental observations.